(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The purpose of the article is to determine the principles of mental training of handball players by means of a questionnaire. Various forms of questions, stressful situations that arise for handball players during training and competitions, as well as ways to eliminate them are presented.Regarding the psychological training of handball players, a questionnaire and statistics of responses, an analysis of scientific and methodological literature are given, the relevance of the topic, purpose, conclusions and recommendations are given.